Influence of Indian Chettiyar Community Heritage on Chettie House Architecture of Malaysia (International Journal of Built Environment and Sustainability, 2024)
The Indian Chettinadu cultural legacy was introduced to Malaysia by Indian merchants who made their home there. The aim of this research is to examine the impact of Indian Chettinadu culture on the architecture of Chetti Melaka houses in Malaysia, as well as its continued significance in the modern era. A qualitative approach is used. There was observation, documentation, and open-ended interviewing. There is documentation about the Chetti's residence at Gajah Berang, Melaka, Malaysia, and the Chettiyar residence in Pallathur, Karaikudi, India. To comprehend how users, Chettiyar culture, and architecture relate to one another, the data triangulation method is used. The findings demonstrate how Indian Cettinadu culture has influenced Malaysian home design. But there is an enormous concession made about the size of the house and intricate decorations. In both situations, the local climate and user requirements have an impact on the house's design. The study's findings are used to propose house design guidelines that might be used in a modern setting.
Keywords: Chetti Community, Cultural Heritage, House Design, Spatial Organization, Architectural Expressions